Proceso de atención de enfermería en paciente femenino de 38 años de edad con artritis reumatoides - Guaquipana Patín, Washington Geovanny (2019)
Rheumatoid arthritis is a chronic inflammatory disease, autoimmune nature characterized by joint manifestations such as pain, swelling and stiffness such as general symptoms, feeling of fever, light discomfort and weight loss, and with the passage of time it is common to see some extra-joint manifestations. In today's world it affects 0.4 - 1.3% of the population throughout the country, most of it occurs frequently in women than in men in ages like 30 and 80 years of age. The cause of this disease is rheumatoid arthritis. of an autoimmune disease, this defines that the human body's immune system mistakenly attacks healthy tissues. The cause of rheumatoid arthritis remains unknown although there is evidence that could be triggered by an infection in genetically predisposed individuals, age and sex are two primary factors associated with rheumatoid arthritis although the onset of the disease can take place in any Peak age of onset is usually during the third age of life. Complications due to rheumatoid arthritis can affect almost any part of the body, such as damage to the lung tissue, injury to the spine when the neck bones are damaged, swelling and inflammation of the outer lining of the heart, pericarditis. The treatment currently does not cure in the disease, although it significantly relieves the intensity of the manifestations, reduce or even stop the activity.